Prognostic value of combining E-cadherin, p53, Bcl-2 and Bcl-xL expression and survival in Tunisian colorectal adenocarcinoma patients : E-cadherin, p53, Bcl-2 and Bcl-xL and colorectal adenocarcinoma - Jamai, Dhouha; kallel, Imen; Mekrezi, Saoussen; walha, Marwa; Gharsallah, Marouan; Khabir , Abdelmajid; Selmi, Boulbaba (Cellular and Molecular Biology, 2022)
Colorectal cancer (CRC) is a common health issue worldwide with an extremely low survival rate after relapse. This study aims to evaluate the immunohistochemical expression of p53, E-cadherin, Bcl-2 and Bcl-xL and find a potential correlation between these markers, clinicopathological factors and overall survival of colorectal cancer patients. Marker expression was immunohistochemically determined in 105 patients with colorectal adenocarcinoma from southern Tunisia, followed by statistical analysis. Positivity rate of nuclear p53, membranous E-cadherin and cytoplasmic Bcl-2 - Bcl-xL was 85.71%, 76.47%, 59.8%, and 85.71% respectively. Spearman correlation showed that p53 was significantly and positively related to E-cadherin, Bcl-2, Bcl-xL and distant metastasis. A positive significant correlation between E-cadherin and anti-apoptotic proteins was also seen. Membranous E-cadherin expression was significantly and negatively associated to poor prognosis factors including lymph node metastasis, lymph invasion, venous invasion and distant metastasis. Bcl-2 expression was significantly correlated to distant metastasis. Multivariate analysis showed a significant association between dependent variable E-cadherin and covariates including differentiation, lymph invasion, venous invasion, distant metastasis, Bcl-2 and Bcl-xL. Poor 3-years OS and 5-years OS were significantly related to p53, Bcl-2 expression and E-cadherin loss. Positive E-cadherin combined with negative p53 and Bcl-2 as well as double-positive for E-cadherin and Bcl-xL were associated to best overall survival. Although each protein can be an independent prognostic factor, Simultaneous E-cadherin, p53, Bcl-2, Bcl-xL expression could be a crucial prognostic and overall survival marker to CRC patients. Multivariate analysis confirmed a positive correlation between membranous E-cadherin loss and colorectal cancer severity.